HBR's 10 must reads on managing yourself (Boston, Mass., 2010)
This collection of best-selling articles includes: bonus article “How Will You Measure Your Life?” by Clayton M. Christensen, "Managing Oneself," "Management Time: Who's Got the Monkey?" "How Resilience Works," "Manage Your Energy, Not Your Time," "Overloaded Circuits: Why Smart People Underperform," "Be a Better Leader, Have a Richer Life," "Reclaim Your Job," "Moments of Greatness: Entering the Fundamental State of Leadership," "What to Ask the Person in the Mirror," and "Primal Leadership: The Hidden Driver of Great Performance."
Keywords: Management; Quản lý